Analisis Perbedaan Gelombang Bunyi Pada Air dengan Software "Frequency Counter" - Vania Yoni Fahmala; Salma Butsainah Salsabila; Khafidh Nur Aziz (JFT: Jurnal Fisika dan Terapannya, 2024)
The process of learning physics can be in the form of conducting a research or experiment so that the results will become a new understanding concept contained therein. The use of the experimental method is intended to be able to observe directly various kinds of phenomena that occur in physics. The purpose of this study is to observe the difference in sound from each glass filled with water with a different volume, to analyze the frequency and period, and to describe the phenomena that occur in experiments with the help of ’’frequency counter’’ software. This experiment was carried out by filling three glasses with water of different volumes and hitting one side of the glass using a weight attached to a support with a rope. Simultaneously operate the ’’frequency counter’’ software to determine the difference in frequency of each glass. The research results obtained, the three glasses produce sounds that have different frequencies and periods, namely for the first glass (1758.21 Hz); (0.73672 m/s), second glass (2158.35 Hz); (0.45727 m/s), third glass (2170.69 Hz); (0.39740 m/s). Also, the phenomenon that occurs is diffraction (bending).